1996
DOI: 10.1063/1.872003
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional radiation-magnetohydrodynamic simulations of SATURN imploding Z pinches

Abstract: Laboratory are modeled with a two-dimensional radiation magnetohydrodynamic ͑MHD͒ code, showing strong growth of the magneto-Rayleigh-Taylor ͑MRT͒ instability. Modeling of the linear and nonlinear development of MRT modes predicts growth of bubble-spike structures that increase the time span of stagnation and the resulting x-ray pulse width. Radiation is important in the pinch dynamics, keeping the sheath relatively cool during the run-in and releasing most of the stagnation energy. The calculations give x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…Therefore, there is clearly a need for high resolutioxL time-gated diagnostics which can be used to test current 2D radiation MHD models (2). In this paper we present the first high-resolutio~time-resolved measurements of a Z-pinch plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is clearly a need for high resolutioxL time-gated diagnostics which can be used to test current 2D radiation MHD models (2). In this paper we present the first high-resolutio~time-resolved measurements of a Z-pinch plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The more recent development of the X-pinch might ease that difficulty. Also, further work on z-pinch stability [7] showed that, while the high density portions of the pinch might be resistively stabilized, the low density edge remains unstable. It is well known from MHD theory that at low β, where β is the ratio of plasma to magnetic pressures, curvature or gravitational instabilities (e.g., sausage and Rayleigh Taylor modes) become electrostatic in nature.…”
Section: Fast Ignitionmentioning
confidence: 99%
“…[3] Cylindrical z-pinches are also being used as radiation sources for indirectly driving fusion pellets via ablation. [4,5,6] Direct-drive quasi-spherical z-pinch compressions offer several advantages over x-ray ablatively driven pellets as fusion drivers. One advantage is efficiency.…”
Section: Layout Ofmentioning
confidence: 99%